The Monetary Transmission in Dollarized and Non-Dollarized Economies : The Cases of Chile, New Zealand, Peru and Uruguay - Acosta Ormaechea, Santiago (IMF Working Papers; Working Paper ;, 2011)
The paper conducts a comparative study of the monetary policy transmission in two economies that run a well-established IT regime, Chile and New Zealand, vis-a-vis two economies operating under relatively newer IT regimes, and which are exposed to a significant degree of dollarization, Peru and Uruguay. It is shown that the traditional interest rate channel is effective in Chile and New Zealand. For Peru and Uruguay, the exchange rate channel is instead more relevant in the transmission of monetary policy. This latter result follows from the limited impact of the policy rate in curbing inflationary pressures in these two countries, in combination with the fact that they have a relatively large and persistent exchange rate pass through. Finally, it is shown that the on-going de-dollarization process of Peru and Uruguay has somewhat strengthened their monetary transmission through the interest rate channel.